Three Phase Partitioning of Serine Protease from Ash Gourd (Benincasa hispida), Its Characterization and Application on Whey Protein Hydrolysis - Khadka, Dambar Bahadur; Adhikari, Laxmi; Khadka, Pragya; Sharma, Alina; Sharma, Abhishek; Karki, Dhan Bahadur (Himalayan Journal of Science and Technology, 2024)
Protease from the ash gourd was purified and concentrated in a one step, applying the three phase partitioning (TPP) methods after optimizing the partitioning factors: saturation level ammonium sulfate, ratio of extract: t-butanol, pH and temperature. The recovered protease (AGP) was characterized and further evaluated for whey protein (0.6%, w/v) hydrolysis ability at varying enzyme concentrations (0-8%, v/v). The ammonium sulfate (50% saturation), the ratio of crude extract: t-butanol (1:1, v/v), 8 pH and 25°C temperature allowed achievement of 122.67 % activity recovery and 5.17 purification fold. The AGP was mainly partitioned at interfacial phase and was serine protease, had a molecular weight of 67.39 kDa. The enzyme performed optimally at temperatures of 60-70°C and pH ranges of 7-9 and demonstrated stability across pH ranges of 5-11 and temperatures up to 70°C. The Km and Vmax value were 1.48 mg/mL and 5.28 µmol tyr/ml/min respectively. Additionally, AGP displayed effective hydrolysis of whey protein, exhibiting higher DPPH radical scavenging and ABTS inhibition activities than un-hydrolyzed and trypsin hydrolyzed whey protein concentrate. This work suggested TPP as a low-cost effective alternative for purification and concentration of AGP, and it could be applied for whey protein hydrolysis to improve the antioxidant activity.